A randomised, double-masked, placebo-controlled trial evaluating the efficacy and safety of teprotumumab for active thyroid eye disease in Japanese patientsResearch in context - Yuji Hiromatsu; Eri Ishikawa; Ai Kozaki; Yasuhiro Takahashi; Mika Tanabe; Ken Hayashi; Yukihiro Imagawa; Kazutoyo Kaneda; Masashi Mimura; Xiaoxian Dai; Tomoko Hayashida; Takashi Akamizu (The Lancet Regional Health. Western Pacific)
Summary: Background: Teprotumumab significantly improved proptosis and diplopia in patients with active, moderate-to-severe thyroid eye disease (TED) in previous North American and European studies. This is the first evaluation of efficacy and safety of teprotumumab for active, moderate-to-severe TED in Japanese patients. Methods: This randomised, double-masked, placebo-controlled trial was conducted in 16 centres in Japan. Main inclusion criteria were as follows: age 20–80 years; Graves’ disease, in a euthyroid or mild hypo/hyperthyroid state; clinical activity score (CAS) ≥3; moderate-to-severe TED; ≥3-mm increase in proptosis before TED onset and/or proptosis ≥18 mm at baseline; and TED duration ≤9 months. Patients were randomised (1:1, stratified by smoking status) to either teprotumumab or placebo. Patients received eight intravenous infusions, one every three weeks for 24 weeks. Patients, investigators, site personnel (except formulating pharmacists) were masked. Primary endpoint was proptosis responder rate (percentage of patients with ≥2-mm proptosis reduction from baseline) at week 24 in the intent-to-treat population. Adverse events were assessed in all patients. This trial was registered at Japan Registry for Clinical Trials (jRCT2031210453). Findings: Fifty-four patients were randomised (teprotumumab, 27; placebo, 27) between February and November 2022. All patients completed the randomised period, although one teprotumumab patient and two placebo patients missed ≥2 doses. At week 24, the proportion of patients with proptosis response was higher in the teprotumumab group (89%, 24/27) compared with the placebo group (11%, 3/27), 95% confidence interval, 61–95; P<0.0001. Study drug-related adverse events (AEs) occurred in 14 patients (52%) in the teprotumumab group and two patients (7%) in the placebo group; hyperglycaemia-related events were reported in six (22%) and one patient (4%), and hearing impairment in four (15%) and one (4%) patient, respectively. Study drug-related serious AEs and deaths were not reported. Interpretation: Teprotumumab significantly improved proptosis compared with placebo in Japanese patients with active TED. No study drug-related serious AEs were observed. Funding: Horizon Therapeutics plc (now Amgen).